The effect of realia on descriptive text writing quality at the eighth grade students of SMPN 1 Bendo - Risky Alif Widayanti (English Teaching Journal : A Journal of English Literature, Language and Education, 2018)
This research is conducted to explain about the Effect of Realia on Descriptive Text Writing Quality at The Eight Grade Students of SMPN 1 Bendo. The sample of this research are 8-K consisted of 21 students in the eighth grade of SMPN 1 Bendo. The research approach that is used in this study is quantitative. The research was conducted by using experimental research. The data was collected by doing test. The technique of data analysis that is used in this research is paired sample T-test. The result of this research shows that Realia gives significant effect to the students’ writing quality in descriptive text. It can be seen that the significant value is 0.000. It shows that the probabilities value of students’ writing skill is lower than 0.05 (0.000<0.05) level of significant. So, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It can be stated that there is significant difference on the students’ descriptive text writing skill before being taught using Realia and after being taught using Realia. So, it can be concluded that Realia helps the students in the process of writing descriptive text and this media has positive effect on the students’ descriptive text writing quality.